Pedicularis khoiyangii (Orobanchaceae), a new species from the Eastern Himalaya, India - Borah, Dipankar; Gap, Neelam; Singh, Rajeev Kumar (Phytotaxa, 2020)
Pedicularis khoiyangii D.Borah & R.Kr.Singh, is described as a new species from the Eastern Himalaya, India. The new species belongs to Pedicularis series Rudes Prain and is closely related to P. prainiana Maximowicz, but differs by its larger size, longer inflorescence, distal bracts ovate, shorter pedicels, smaller calyx, densely silky villous nature, calyx teeth shorter with entire margins, equal, smaller corolla tube, shortly beaked galea, tip slightly emarginate, labium as long as galea, lobes unequal, stamens inserted at the base of corolla tube, style projecting out of the galea. This is the tallest species of Pedicularis recorded so far from India.